Instructional teaching theory: Basis for effective teaching device in learning - Leovigildo Lito D. Mallillin (S&Co Publishing, 2024)
The study examines the contribution of instructional teaching theory in educational system as a basis for effective teaching devices in learning as to print materials, electronic media, technology devices, visualization and graphics, games, and interactive resources. The study employs descriptive quantitative research designs because it measures and quantifies the variables of the study on the contribution of instructional teaching theory in educational system. Likewise, convenience purposive sampling is utilized in the study. It is a non-probability sampling method in gathering the sample size of the study. The study comprised one hundred seventy five (175) respondents only. Results show to offer and plan step by step lesson, time saving, assessment materials, testing, and worksheets, to create and allow multiple friendly learning for students to listen in audiobooks, CDs, using headset to avoid disturbance from other classmates, show to help and develop deeper learning and understanding process of students, and show learning factor on the concept of instructional teaching that can turn complex things into play. Findings show that there is a significant correlation on the contribution of instructional teaching theory in educational system as a basis for effective devices in learning as observed by the respondents.